A filtering monotonization approach for DG discretizations of hyperbolic problems. (1st January 2023) - Orlando, Giuseppe
Abstract: We introduce a filtering technique for Discontinuous Galerkin approximations of hyperbolic problems. Following an approach already proposed for the Hamilton-Jacobi equations by other authors, we aim at reducing the spurious oscillations that arise in presence of discontinuities when high order spatial discretizations are employed. This goal is achieved using a filter function that keeps the high order scheme when the solution is regular and switches to a monotone low order approximation if it is not. The method has been implemented in the framework of the deal.II numerical library, whose mesh adaptation capabilities are also used to reduce the region in which the low order approximation is used. A number of numerical experiments demonstrate the potential of the proposed filtering technique. Highlights: Filtering technique for hyperbolic problems. Monotonization for high order DG polynomials. Combination with adaptive grid.